Ageing Workforces, Ill‐health and Multi‐state Labour Market Transitions. (1st August 2020) - Harris, Mark N.; Zhao, Xueyan; Zucchelli, Eugenio
Abstract: We provide novel evidence on the effects of ill‐health on the dynamics of labour state transitions by considering retirement as mobility between full‐time work, part‐time work, self‐employment and inactivity. We employ a dynamic multi‐state model which accounts for state dependence and different types of unobservables. Our model allows for both individual heterogeneity and labour‐state gravity as well as correlations between labour market states. We estimate this model on rich longitudinal data from the Household, Income and Labour Dynamics in Australia Survey. We find that both ill‐health and health shocks greatly increase the probability of leaving full‐time employment and moving into inactivity. Simulated dynamic trajectories suggest larger impacts of long‐term health conditions than those of a one‐off health shock and some evidence of health‐driven retirement pathways via part‐time work and self‐employment. Our findings also indicate that the effects of health changes could be underestimated and the magnitude of true labour market state dependence overestimated if individual effects or labour dynamic transitions are not accounted for in the model.